Las micro y pequeñas empresas y su desarrollo empresarial en la provincia de Huánuco - Miraval Tarazona, Cayto (2017)
This research on formalization of MSEs and business development of the province of Huanuco, has allowed us to learn about the scenario in this sector of the local economy unfolds. Laws exist in order to promote micro and small companies, making market entry and competitiveness, however there are institutions that are required by law to that task, but do not meet the legal provisions in this regard, as the Municipality and the Regional Government, being a situation of inconsistency between laws establishing itself and what happens in reality, thus slowing, business development which requires the city and the region of Huanuco.